2020
DOI: 10.3390/ijms21228843
|View full text |Cite
|
Sign up to set email alerts
|

Recent Discoveries on the Involvement of Krüppel-Like Factor 4 in the Most Common Cancer Types

Abstract: Krüppel-like factor 4 (KLF4) is a transcription factor highly conserved in evolution. It is particularly well known for its role in inducing pluripotent stem cells. In addition, KLF4 plays many roles in cancer. The results of most studies suggest that KLF4 is a tumor suppressor. However, the functioning of KLF4 is regulated at many levels. These include regulation of transcription, alternative splicing, miRNA, post-translational modifications, subcellular localization, protein stability and interactions with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 167 publications
(264 reference statements)
0
26
0
Order By: Relevance
“…Previous reports showed that KLF4, a zinc finger-type transcription factor, played a pivotal and different role in the development of various cancers, including lung cancer, HCC, and pancreatic cancer [ 44 48 ]. However, low expression of KLF4 promoted the growth, invasion, and metastasis of NSCLC, but high expression of KLF4 displayed a valuable role for therapy of NSCLC [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that KLF4, a zinc finger-type transcription factor, played a pivotal and different role in the development of various cancers, including lung cancer, HCC, and pancreatic cancer [ 44 48 ]. However, low expression of KLF4 promoted the growth, invasion, and metastasis of NSCLC, but high expression of KLF4 displayed a valuable role for therapy of NSCLC [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Krüppel-like factor 4 (KLF4) can inhibit the development of tumor by associating with the non-Warburg metabolic behaviors (Blum et al, 2021). Low expression of KLF4 may lead to poor prognosis and link to the progression of COAD (Taracha-Wisniewska et al, 2020). T-cell factor 7-like 1 (TCF7L1) has been found to have a high expression in many cancers, such as breast cancer and skin squamous cell carcinoma (Slyper et al, 2012;Ku et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 is a stem cell factor which, together with octamer-binding transcription factor 4, SOX2, homeobox protein NANOG and transcription factor MYC, is involved in the induction of pluripotent stem cells (97). Most studies suggest that KLF4 acts as a tumor suppressor, but protumorigenic activity of KLF4 has also been reported (98). KLF4 promoted ESCC differentiation by up-regulation of keratin 13 expression (99).…”
Section: Mirs Targeting Transcription Factorsmentioning
confidence: 99%